2019
DOI: 10.1038/s41419-019-1395-6
|View full text |Cite
|
Sign up to set email alerts
|

MiR-210-3p protects endometriotic cells from oxidative stress-induced cell cycle arrest by targeting BARD1

Abstract: Endometriosis is associated with benign but adversely developed cysts in the extrauterine environment. The oxidative imbalanced environment induces DNA damage and affects cell cycle progression of endometrial stromal cells (ESCs) and endometrial epithelial cells, but how endometriotic cells maintain proliferation in the presence of oxidative stress is not clear. Growing evidence has indicated that the ectopic hypoxic microenvironment and oxidative stress can stimulate the growth of endometriotic cells, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 49 publications
1
31
1
Order By: Relevance
“…Additionally, in another ongoing study, we showed that miR-130a significantly induces porcine GC apoptosis and follicular atresia by targeting the TGF- β signaling pathway (data not shown). Moreover, several DEmiRNAs, such as miR-141 and miR-210, have been proven to control oxidative stress responses in ovarian cancer cells and endometriotic cells by targeting p38α and BARD1 , respectively [67, 68], suggesting that several identified DEmiRNAs may function as modulators in response to oxidative stress. We also identified 19 novel, function-unknown DEmiRNAs which require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in another ongoing study, we showed that miR-130a significantly induces porcine GC apoptosis and follicular atresia by targeting the TGF- β signaling pathway (data not shown). Moreover, several DEmiRNAs, such as miR-141 and miR-210, have been proven to control oxidative stress responses in ovarian cancer cells and endometriotic cells by targeting p38α and BARD1 , respectively [67, 68], suggesting that several identified DEmiRNAs may function as modulators in response to oxidative stress. We also identified 19 novel, function-unknown DEmiRNAs which require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, extended longevity, resulting in a higher median age for women, results in a promulgation of these effects such that DNA or oxidative damage and other DNA/RNA/ miRNA mutational events accumulate in affected cells and so create the focus for endometrial hyperplasia that is a precursor for the early stage development of EC [ 87 , 88 ]. This early stage EC (type 1, grade 1) is particularly difficult to detect, as such patients are often asymptomatic.…”
Section: Mechanisms Of Oestrogen-induced Endometrial Cancermentioning
confidence: 99%
“…Hypoxia inducible factor (HIF)-1α is a key regulator of hypoxia, which makes it a useful marker of cellular hypoxic stress. Our previous studies revealed that HIF-1α expression was increased in ectopic lesions compared with that in eutopic tissues and normal endometrium (7,8). Ectopic endometrial cells may ultimately use the hypoxic microenvironment to promote cell adhesion, proliferation and angiogenesis (5,6); however, how ectopic cells convert the metabolism to overcome and adapt to hypoxic microenvironments before new vasculature forms in ectopic lesions is not clear.…”
Section: Introductionmentioning
confidence: 99%